COVID-19 vaccine hesitancy among rural Oklahomans - Randolph Hubach; Bryan Shannon; Kerry Morgan; Caleb Alexander; Andrew O'Neil; Campbell Ernst; Zachary Giano (James Cook University, 2022)
Introduction: COVID-19 vaccination is widely recommended as a prevention strategy; however, vaccine uptake is disproportionately lower among rural Americans compared to their urban counterparts. Development of public health activities to address the rural-urban vaccine gap requires an understanding of determinants of vaccine hesitation. The present study explores perceptions of and barriers to COVID-19 vaccination among rural Oklahomans. Methods: Between March and May 2021, 222 residents, unvaccinated for COVID-19, within rural Oklahoma counties completed a cross-sectional, online questionnaire to qualitatively assess perceptions, benefits, and concerns regarding getting vaccinated for COVID-19. Results: Approximately two-fifths of rural respondents in the present study were hesitant to get vaccinated, even when a vaccine was made available to them. Major factors included limited knowledge and understanding about the vaccine, including potential side-effects and long-term complications, as well as skepticism surrounding COVID-19 vaccine development and efficacy. Among the potential perceived benefits of vaccination were protecting the health of vulnerable individuals and the ability to return to normal day-to-day activities. Conclusion: Increases in COVID-19 cases and deaths in rural areas are expected to continue as new variants are introduced within communities. The present findings highlight the need for the development of culturally tailored vaccine information, to be disseminated by local leaders within rural communities.